The impact of perioperative anemia on postoperative delirium after hip fracture surgeries in older adults: a multicenter retrospective cohort study - Xu, Xin; Xu, Peng; Wang, Junxiang; Yu, Hui; Li, Yanan; Zhang, Qi; Wang, Tao; Long, Yubin; Li, Erliang; Wang, Jiachen; Xie, Jiale; Guo, Junfei (Frontiers in Nutrition, 2026)
BackgroundPostoperative delirium (POD) is a frequent yet underestimated neurocognitive complication following hip fracture surgery, particularly among older adults. While anemia is a prevalent and potentially modifiable nutritional disorder in this population, but its impact on POD remains uncertain. We aimed to examine the association between perioperative anemia and POD risk in older adults undergoing surgical treatment for intertrochanteric fractures (ITF).MethodsWe conducted a multicenter retrospective cohort study of elderly patients with ITF who underwent surgical fixation in China. Patients were categorized by their nadir perioperative hemoglobin (Hb): ≥103 g/L, 75–<103 g/L, and <75 g/L. Propensity score matching (PSM) with a 1:1:1 optimal algorithm was used to balance baseline variables. Participants were followed for up to 24 months. POD incidence was assessed and compared across groups. We used multivariable logistic regression to identify independent predictors and performed exploratory mediation analyses.ResultsAmong 1,694 patients, the overall POD incidence was 9.7%. After PSM, POD incidence differed across Hb groups: 12.4% (<75 g/L), 2.9% (75–<103 g/L), and 7.6% (≥103 g/L). Multivariate analyses identified severe anemia (OR: 3.13; 95% CI: 1.59–6.18; p < 0.001), preoperative transfusions (OR: 1.67, 95% CI: 1.02–2.74, p = 0.042), and transfusion volume (OR: 1.39, 95% CI: 1.02–1.89, p = 0.037) as independent predictors of POD. Exploratory mediation analyses showed the lowest perioperative Hb levels accounted for 55.9% of the effect of anemia on POD, with preoperative transfusions and transfusion volume accounting for 35.4 and 8.7%, respectively.ConclusionSevere perioperative anemia is strongly associated with increased POD risk in older adults with ITF, independent of other clinical factors. Optimizing perioperative anemia management should be a central component of surgical care and POD prevention strategies in geriatric orthopedic populations.